1989
DOI: 10.1002/pc.750100508
|View full text |Cite
|
Sign up to set email alerts
|

Delamination shape effects in aramid‐epoxy‐aluminum (ARALL) laminates with fatigue cracks

Abstract: An aramid reinforced aluminum-epoxy-laminate, ARALL, which contains a fatigue crack and a delamination zone is analyzed. It is assumed that the interlaminar shear forces between the aluminum and aramid/epoxy layers are transmitted along the delamination boundary. The aramid/epoxy layer of the laminate is considered a series of linear springs. The tensile stress in the aramid/epoxy layer and the stress intensity factor in the aluminum layer are found for various experimentally observed delamination shapes. A re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1991
1991
2007
2007

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…He verified the claims of Delft and Marrisen that fiber bridging was successful when promoted by controlled delaminations and that a significant "bridging zone" of 3-5 mm resulted. J. Macharet [21] of ALCOA Laboratories conducted an extensive research on the delamination shape in ARALL and showed that the larger the delamination area in the longitudinal direction, the less effective the fibers are in bridging and slowing crack growth. Davidson and Austin [20], using single edge notched specimens of ARALL, also showed a marked superiority of ARALL over monolithic aluminum due to fiber bridging at high AK levels.…”
Section: Adhesive Shear Deformationmentioning
confidence: 99%
“…He verified the claims of Delft and Marrisen that fiber bridging was successful when promoted by controlled delaminations and that a significant "bridging zone" of 3-5 mm resulted. J. Macharet [21] of ALCOA Laboratories conducted an extensive research on the delamination shape in ARALL and showed that the larger the delamination area in the longitudinal direction, the less effective the fibers are in bridging and slowing crack growth. Davidson and Austin [20], using single edge notched specimens of ARALL, also showed a marked superiority of ARALL over monolithic aluminum due to fiber bridging at high AK levels.…”
Section: Adhesive Shear Deformationmentioning
confidence: 99%
“…: -;-82314005283, Fmc: +82 31406 5550 E-mail address:oschoi@hanyang.ac.kr tion due to the occurrence of local cavities in the FRP layer during the curing process, and to the formation of residual stress caused by their different thermal contractions between the Al and fiber layers. Although some kinds of FMLs are commercially available by the trade name of GLARE [8,9] or ARALL [10][11][12][13][14] their fracture characteristics and mechanisms associated with the Al kind, notch existence and fiber orientation are not sufficiently verified as tar as the authors know. Recently, the studies on FMLs have mainly focused on fatigue or impact characteristics of FMLs whose constituent fiber layer was unidirectional [8, 9,13,14].…”
Section: Introductionmentioning
confidence: 99%
“…Although some kinds of FMLs are commercially available by the trade name of GLARE [8,9] or ARALL [10][11][12][13][14] their fracture characteristics and mechanisms associated with the Al kind, notch existence and fiber orientation are not sufficiently verified as tar as the authors know. Recently, the studies on FMLs have mainly focused on fatigue or impact characteristics of FMLs whose constituent fiber layer was unidirectional [8, 9,13,14]. To apply FMLs in automobile components and infrastructures, further studies in relation to basic mechanical properties and fracture toughness of FIvILswith various lay-up angles should be carried out for their safety, integrity and reliability.…”
Section: Introductionmentioning
confidence: 99%